Faculty expectations of administrative leaders behavior (department chairs) at the University of Belize - Ogaldez, Theodore J. M., author; Richburg, Robert, advisor; Miser, Keith, advisor; Shang, Paul, committee member; Aukerman, Robert, committee member (Colorado State University. Libraries, 2003)
The author conducted an extensive literature review to examine the type of leadership that would be needed on The University of Belize's campuses in order to help such a new institution win acceptance at home and abroad. The tool used in the study was the Leader Behavior Description Questionnaire (LBDQ), which was developed on the Ohio State University campus. In this study the instrument was used to measure ideal behavior. That is, the type of leader behavior the faculty at University of Belize would like to see in their department chairs. The researcher distributed one hundred surveys and obtained 64% return rate. SPSS software was used to compute frequency tables to answer the descriptive research questions identified in the study. The other four questions, which are comparative, were answered using one-way ANOVA and t-test. Within the Literature review the author highlighted some characteristics, which people generally expect to see in the persons they consider good leaders. The fact that Belizean people on a whole view their leaders with a certain degree of skepticism make it important for department chairs to be given some kind of training in administration before they assume the position. It is also important that the faculty don't perceive the existence of a gap between them and the department chairs that make it impossible for them to communicate. The survey results showed no significant statistical difference between the two dimensions of leader behavior for any of the five questions asked. For each of the five questions the dimension of consideration and initiating structure both received a rating of 3 on a scale of 0 to 4, with 3 representing a response of "often." The author deduced from these consistent ratings that the faculty wanted their department chairs to often exhibit a balance between consideration and initiating structure. That means that the faculty wanted the department chairs to take the lead in helping them to achieve the goals of the department. They, however, wanted an open door relationship with their department chairs, which would allow them to approach their department chairs at anytime to give suggestions or seek solutions for problems they were experiencing. The findings from the experiential questions were reinforced by the answers from the two open-ended questions, where faculty stated that they would like department chairs to develop an agenda for the department with input from the faculty. It was also stated in reply to one of the open-ended questions that the faculty would like to get to know each other and their department chair outside of the normal working hours. They would like social events and recognition for work done beyond the normal call of duty. The author ended by making suggestions for how department chairs within the new University of Belize can help create a stable environment for themselves and the faculty. He suggested that new department chairs be given training in management and relationship building, and that governmental involvement within the institution be limited to that which is necessary.
Keywords: higher education